Analysis of Dual Polarization Characteristics of Turbulent Structure from Hail Supercell Storms - Juxiu WU; Ming WEI; Xiuguang DIAO; Jiawen PAN (Gaoyuan qixiang)
Convective storms transmit momentum through turbulence， so it is important to understand the echo characteristics of turbulence structure in severe convective storms.Focusing on the velocity spectrum width above 5 m·s -1， the turbulent intensity of two strong hailstorm supercells with different intensity of mesocyclones are analyzed， and the relationship between airflow structure and turbulence enhancement are revealed.The results show that： （1） The strong hail supercell has moderate or above intensity turbulence in the strong updraft region， and the supercell triggered by the gust front also shows moderate intensity spectrum width in the inflow path， indicating the possibility of moderate intensity turbulence.（2） In general， the strongest turbulence occurs in the region with the largest velocity shear intensity.The maximum spectrum width of the supercell with moderate intensity mesocyclone is about 10 ms -1， with differential reflectivity factor （ ZDR） within 1dB， echo intensity exceeding 35 dBZ， and larger differential phase shift rate （ KDP）.The strong turbulence region of the supercell with strong mesocyclone is mainly located at the intersection of positive and negative velocities at the top of ZDR column， and the spectral width near the mesocyclone can reach 16.5 m·s -1， and the side near the strong echo core contains more supercooled water， with about 0.96 of correlation coefficient （CC） and large KDP.While， the echo intensity on the other side is slightly lower， with CC low to 0.85， where graupel particles and large raindrops brought by updraft exist.These regions of strong turbulence indicate the path of momentum transmission.（3） The upper part of the supercell storm has the strongest turbulence， both updrafts and downdrafts are strong， but the turbulence is stronger near the downdrafts that probably related to horizontal shear of the wind， where the highest spectrum width for strong mesocyclone is 17.5 m·s -1， and ZDR is higher than that in the updraft and KDP is negative， but KDP is about 0 （°）·km -1 and ZDR is about 0 dB in the updrafts， however， spectrum width of the storm with moderate mesocyclone increases slightly.Strong mesocyclone supercell has stronger turbulence enhancement， and these discussions provide a reference for understanding the turbulence structure and momentum transmission of severe storms by dual-polarization radar observation.